Pengaruh Indikator Makroekonomi terhadap Indeks SRI-KEHATI yang Dimoderasi Variabel Konfirmasi Kasus COVID-19 - Kho, Celine; Yulfiswandi, Yulfiswandi (Jurnal Manajemen Bisnis dan Keuangan, 2024)
The capital market is one of the most critical factors in developing the Indonesian economy and can be used as a medium for investing. In Indonesia, the SRI-KEHATI Index is currently attracting much attention. Macroeconomic factors such as the exchange rate, inflation rate, amount of money in circulation, Monday effects, and Friday effects are variables that are quite often mentioned in their influence on stock indices, especially during the pandemic. After the COVID-19 pandemic, the capital market has been experiencing fluctuations and depreciation. This research aims to test the influence of Monday effects, Friday effects, interest rates, inflation rates, and the amount of money in circulation on stock indices with COVID-19 as a moderation. Using the multiple linear regression method, the number of samples used in this research was 958, which is monthly data from January 1, 2019, to November 30, 2022. The research results show that the variables of interest rates, money supply, and the COVID-19 pandemic significantly influence the SRI-KEHATI Index. In contrast, the Monday effect, Friday effect, and inflation variables do not have a significant effect.